(untitled) (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2022)
The purpose of this study is to find out how the problems of women in the struggle for religious domination occur due to the interpretation of the verses of the Qur'an by negating women in it. Nawal El-Sa'dawi wrote this description in the novel “the fall of the imam”. For him, this problem is the entry point for all forms of oppression of women under the protection of Islam, so the novel is a form of resistance and criticism of the phenomena that occur. Asghar regarding the liberation of women that interpretation must be in accordance with the values ​​of justice and humanity. Starting from the three frameworks of Asghar's thinking, where interpretation must be normative, interpretative, and open throughout the ages. This research is a descriptive qualitative research by using “the fall of the imam” as the primary data of the study. Meanwhile, the perspective of Asghar women's liberation is used as a tool to analyze the formation of inequality against women due to interpretations in patriarchal culture. The results found there are three important aspects. First, religion and patriarchal culture, how patriarchal culture becomes the main point of patriarchal interpretation. Second, women's resistance to religious dogmatism. The resistance shown by Nawal is an attempt to liberate women. Third, Nawal's redefinition of women to achieve equality in various fields of social order, because of the contamination of interpretations scattered in religion, must be reconstructed in a new and liberating form.